Adsorptive Elimination of Chromium(III) and Nickel(II) from Water by Spent Eugenia jambolana Leaves: Isothermal and Thermodynamical Studies - Rehman, Rabia; Anwar, Jamil; Mahmud, Tariq (Asian Journal of Chemistry, 2014)
Removal of metal ions from waste-water streams is a hot issue for environmental protection. In this study, adsorption capacity of spent Eugenia jambolana leaves was investigated for removing chromium(III) and nickel(II) from aqueous medium. FT-IR and chemical characterization of Eugenia jambolana leaves helps to investigate the mechanism of adsorption. Adsorption parameters were optimized and isothermal studies were carried out. It indicated that chemisorption mode is more predominant over physiosorption of Ni(II) and Cr(III) with maximum adsorption capacity 6.003 and 3.815 mg/g, respectively. Feasibility of process is confirmed by separation factor values: 0.25 and 0.141 for Ni(II) and Cr(III) correspondingly and Gibb’s free energy values: -6.971 and -5.212 KJ/mol for Ni(II) and Cr(III), respectively. Heats of adsorption for Ni(II) and Cr(III) removal by Eugenia jambolana leaves were -1.349 and -0.0384 KJ/mol, respectively. The results shown that Eugenia jambolana leaves can be used on industrial scale for removal of heavy metals.